Effect of Green Value Cocreation on Consumer Behavior: A Professional Baseball Franchise’s “Sustainable Party” Event - Chen-Yueh Chen; Yi-Hsiu Lin; Ming-Ti Shih; Tzu-Yun Yeh (Behavioral Sciences)
This study examined whether participation in green activities affects the green purchase intention, team identification, and subjective well-being of sports fans through green value cocreation. In addition, this study explored the mediating role of team identification and the moderating role of subjective well-being in green value cocreation. Composite reliability and confirmatory factor analyses were conducted to evaluate the validity and reliability of the research instruments, and structural equation modeling was used to test the study hypotheses. The results indicated that green value cocreation significantly predicted green purchase intention, team identification, and subjective well-being. Team identification partially mediated the relationship between green value cocreation and green purchase intention. However, subjective well-being did not moderate the effect of green value cocreation on green purchase intention. This study investigated how green value cocreation enhances fan participation in environmental actions and translates into green purchase intention. The findings provide insights into the emotional connection between fans and teams and the effect of this connection on green value cocreation and green purchase intention. This study addresses a research gap regarding the role of green value cocreation in professional sports and provides practical insights for businesses, teams, and society to promote environmentally conscious consumption and behavior.